Histopathology of myopic cobblestones - Jonas, Shefali B.; Jonas, Rahul A.; Panda-Jonas, Songhomitra; Jonas, Jost B. (Acta ophthalmologica, 2022)
Purpose To search for the histological correlate of peripheral ‘cobblestones’ in highly myopic eyes. Methods The histomorphometric investigation included histologic sections of enucleated eyes of Caucasian patients. Using light microscopy, we measured the thickness of the retina, Bruch’s membrane (BM) and choriocapillaris. Results The study included 50 eyes (mean age:60.6 ± 18.7 years;axial length:26.5 ± 3.8 mm), with cobblestone regions detected in 7 eyes. BM thickness and choriocapillaris thickness in the cobblestone region were thinner (1.1 ± 0.2 µm versus 2.4 ± 0.8 µm; p < 0.001 and 1.6 ± 0.5 µm versus 2.6 ± 1.9 µm; p = 0.02, respectively), and just outside of the cobblestone region they were thicker (3.3 ± 0.6 µm versus 2.4 ± 0.8 µm; p = 0.005 and 5.7 ± 1.6 µm versus 2.6 ± 1.9 µm; p = 0.002, respectively) than in corresponding regions of eyes without cobblestones. Within the group of eyes with cobblestones, BM thickness (1.1 ± 0.2 mm versus 3.3 ± 0.6 mm; p < 0.001), choriocapillaris thickness (1.6 ± 0.5 mm versus 5.7 ± 1.6 mm; p < 0.001) and choriocapillaris density (48±15 µm/300 µm versus 159 ± 66 µm/300 µm;PP=0.002) were significantly lower in the cobblestone region than just outside of the cobblestone region. The cobblestone regions were characterized by firm adhesion of disorganized retina with thinned BM, few retinal pigment epithelium (RPE) islands within cobblestone regions, and absence of regional scleral or overall choroidal thinning. BM was mono-layered within, and double-layered outside of cobblestone regions, with the inner layer missing within the cobblestone region (except for the RPE islands). Conclusions Peripheral cobblestone regions in highly myopic eyes are characterized by marked BM thinning with absence of an inner BM layer, almost complete RPE absence, choriocapillaris thinning and firm connection of a disorganized retina to BM. These findings may help elucidating the process of axial elongation in myopic eyes.